РІВЕНЬ РОЗЧИННОЇ ІЗОФОРМИ CD150 У ПЛАЗМІ ХВОРИХ НА ХРОНІЧНИЙ ЛІМФОЛЕЙКОЗ - Gordiienko, I.; Scherbina, V.; Shlapatska, L. (PH Akademperiodyka, 2023)
Background. SLAMF1/CD150 is an active player in B cell signaling networks in chronic lymphocytic leukemia (CLL). CD150-mediated signaling initiates through a homophilic CD150 binding, which spans the adjacent cells, or the interaction with the soluble CD150 isoform (sCD150). The expression of sCD150 isoform at the mRNA and protein levels ex vivo was confirmed. However, it is unclear whether sCD150 isoform present in the blood plasma of CLL patients is a factor in the constitutive activation of CD150+ cells. The aim of this study was to develop an ELISA assay for the specific sCD150 evaluation and assess the sCD150 levels in the blood plasma of CLL patients with different CD150 expression on B cells. Materials and Methods. Blood plasma samples and peripheral blood mononuclear cells from 40 previously untreated CLL patients were analyzed. An ELISA method, ex vivo drug sensitivity assay, and a cell viability assay were used. Results. The sCD150 isoform was found in all studied plasma samples of CLL patients at different levels regardless of the cell surface CD150 expression status of B cells and sCD150 mRNA expression. CLL cases with low levels of the cell surface CD150 expression in B cells are characterized by high levels of sCD150 in blood plasma in contrast to the CLL cases with high cell surface CD150 expression on B cells. The elevated levels of sCD150 in blood plasma are associated with a better sensitivity of malignant B cells to cyclophosphamide and bendamustine. Conclusions. The sCD150 isoform is actively secreted by CLL B cells with its accumulation in blood plasma, which may be regarded as an additional factor in the CLL clinicopathologic variability.